Improvement of The Physical Quality of Local Beef with Different Wet Aging Period (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Local cattle in Indonesia generally have lower productivity and meat quality, so fulfilling high-qualitymeat needs still relies on imported supplies. The study aims to explore the potential of lower-qualitylocal beef to be aged so that the quality of local meat can be improved with parameter observed WBSFvalue, pH value, water binding capacity and percentage of cooking loss. This study used the wet agingmethod and the chosen samples of Bali cattle, Ongole crossbred cattle and Simmental crossbred cattlewith aging periods of 1 day, 7 days, 14 days, 21 days and 28 days. Data were analyzed using a split plotsplit in time design. The results showed that aging improves the physical qualities of the beef, namely asignificant decrease in WBSF value, while pH value, water binding capacity and percentage of cookingshrinkage were still within the standard value range despite changes observed within the aging period.Bali cattle achieved tender category (3.9-4.4 kg cm-2) at 14 days aging period (4.08 kg cm-2), while Ongoleand Simmental crossbreds achieved tender category at 21 days aging period (4.27 and 3.76 kg cm-2,respectively)